2022
DOI: 10.1021/acsaem.2c00704
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of BaZrS3 Perovskite Thin Films at a Moderate Temperature on Conductive Substrates

Abstract: Chalcogenide perovskites are being considered for various energy conversion applications, not least photovoltaics. BaZrS 3 stands out for its highly stable, earth-abundant, and nontoxic nature. It exhibits a very strong light−matter interaction and an ideal band gap for a top subcell in a two-junction photovoltaic device. So far, thin-film synthesisnecessary for proper optoelectronic characterization as well as device integrationremains underdeveloped. Sputtering has been considered, among others, but the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
44
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 45 publications
(97 reference statements)
0
44
0
1
Order By: Relevance
“…Comparotto et al utilized sputtering to create a Ba–Zr–S film that was subsequently sulfurized to create BaZrS 3 . Initially needing 900 °C to get high crystallinity, they later found that preventing oxide formation and supplying excess sulfur allowed the temperature to be dropped to around 600 °C. , Finally, low-temperature film fabrication has been achieved by first synthesizing BaZrS 3 at high temperatures and then depositing a film through pulsed laser deposition or by grinding and functionalizing the material to make a colloidal solution that can be coated. However, both methods have only produced films of low crystallinity without further heating. , …”
mentioning
confidence: 99%
“…Comparotto et al utilized sputtering to create a Ba–Zr–S film that was subsequently sulfurized to create BaZrS 3 . Initially needing 900 °C to get high crystallinity, they later found that preventing oxide formation and supplying excess sulfur allowed the temperature to be dropped to around 600 °C. , Finally, low-temperature film fabrication has been achieved by first synthesizing BaZrS 3 at high temperatures and then depositing a film through pulsed laser deposition or by grinding and functionalizing the material to make a colloidal solution that can be coated. However, both methods have only produced films of low crystallinity without further heating. , …”
mentioning
confidence: 99%
“…19 Most promisingly, film growth and crystallization at 600 1C has been achieved using a sputtering/ sulfurization approach. 20 Many of these techniques also require more complex and expensive equipment compared to the solution-phase growth and processing that is possible with the hybrid lead halide perovskites.…”
mentioning
confidence: 99%
“…Chalcogenide perovskiteseponymously named for containing S, Se, or Te as the anion rather than a halideare an emerging frontier in Pb-free, inorganic perovskites with high stability. Promising optoelectronic properties have been identified for this material family, primarily from theory, including band gap values relevant for photovoltaics, a tolerance to deep defects, strong dielectric screening for generating free carriers with a long lifetime, favorable phonon properties for high-performance thermoelectrics, and desirable (isotropic) electron mobility for efficient charge transport. Furthermore, a high density of chalcogenide p -states in the valence band maximum results in an extraordinarily high absorption coefficient, exceeding those of other solar technologies. , Importantly, increased covalent bonding in the crystal lattice relative to that in halide perovskites results in enhanced structural stability. , …”
mentioning
confidence: 99%